2021
DOI: 10.1159/000519072
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Estradiol Effects in MAPK and Akt Cell Signaling across Subregions of the Hippocampus

Abstract: <b><i>Introduction:</i></b> Rapid effects of estrogens within the hippocampus of rodents are dependent upon cell-signaling cascades, and activation of these cascades by estrogens varies by sex. Whether these pathways are rapidly activated within the dentate gyrus (DG) and CA1 by estrogens across sex and the anatomical longitudinal axis has been overlooked. <b><i>Methods:</i></b> Gonadally intact female and male rats were given either vehicle or physiological syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Here, we have elucidated key intracellular mechanisms underlying the rapid facilitation of short-term social memory by E2. ERK and PI3K were previously found to be rapidly activated by estrogens(16,41,42) and necessary for long-term memory enhancements by E2(32,4143,45). Our results suggest that these pathways are also necessary for the rapid enhancement of short-term social memory, thus underlying the adaptive dynamic modulation of social interactions by estrogens at times of changing social milieu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we have elucidated key intracellular mechanisms underlying the rapid facilitation of short-term social memory by E2. ERK and PI3K were previously found to be rapidly activated by estrogens(16,41,42) and necessary for long-term memory enhancements by E2(32,4143,45). Our results suggest that these pathways are also necessary for the rapid enhancement of short-term social memory, thus underlying the adaptive dynamic modulation of social interactions by estrogens at times of changing social milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens have long been known to elicit their effects by binding to intracellular estrogen receptors (ERs) that then dimerize, translocate to the nucleus, and directly affect gene transcription and protein expression (14). In addition to these delayed "classical" effects, estrogens affect molecular (15,16), cellular (17)(18)(19), systems (20,21), and behavioural (22)(23)(24)(25)(26) processes very rapidly (minutes) through intracellular mechanisms including activation of cell signaling cascades, such as the extracellular signal-regulated kinase (ERK) and phosphoinositide 3-kinase (PI3K) cascades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has identified sex-specific differences in AKT isoforms as a key factor in regulating neurobiological processes [ 36 ]. AKT was also differentially phosphorylated in hippocampal samples in the same direction as KRSA predictions [ 37 ]. Finally, another study identified differential expression of AKT-associated genes, but did not find significance in phosphorylation of AKT itself between males and females [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have indicated sex differences for δOR signaling in hippocampal areas (Harte-Hargrove et al, 2015;Mazid et al, 2016). Previous studies have also shown that female mice are more likely to show enhanced AKT phosphorylation, specifically in the hippocampus, in response to estrogen (Sheppard et al, 2021). If this is the case, then it is possible that inhibiting AKT with honokiol in male β-arrestin 1 knockout mice may have less of an effect on SNC80-induced seizures.…”
Section: Figurementioning
confidence: 99%